Miningkatkan Kemampuan Matematika Anak Usia Dini melalui Media Loose Part - Ina Ibna Sholiha; Lia Ulya Hasanah; Syifa Ainurrahmah; Uci Luciana (incrementapedia, 2022)
RA Insan Cendekia Jatisari Permai's observation of children's development revealed that there were problems in arithmetic operations, meaning that most children still had difficulties in performing subtraction operations. Most of the children were still confused about the ability to count, so the results of the activities were below the maximum number of 10 students, only 7 children were able to complete the task without the help of the teacher. The type of research used by researchers is descriptive-qualitative, namely described what the researchers did during the observation. The aim of the observation was to see how math skills used loose media in early childhood RA Insan Scholar Taman Jatisari Permai. This research was conducted qualitatively through observation and interviews with class X children. Based on the above studies, early childhood learning will be fun by using real objects with 7 components made of loose materials. Irtoosamedia's aim is to make children more creative. The results of RA Insan Scholar's research show that 7 out of 10 children experience improvement in basic mathematics.